EXPERIMENTAL DETERMINATION OF CONVECTIVE HEAT TRANSFER COEFFICIENT DURING OPEN SUN AND GREENHOUSE DRYING OF APPLE SLICES - Cerci, Kamil Neyfel; Kavak Akpinar, Ebru (Yildiz Technical Univ, 2016)
A small scale greenhouse type dryer was designed and tested. Convective heat transfer coefficient of apple slices was identified under open sun at natural convection mode and in greenhouse drying at natural and forced convection mode. The experiments were carried out in May-June, 2014 under the climatic conditions of Elazig, Turkey (39 degrees 14' E 38 degrees 41'N). The rate of moisture removal, crop temperature, relative humidity inside and outside the greenhouse and ambient air temperature for complete drying was recorded at 30 min intervals. The values of constants (C and n) in Nusselt number expression were found by using linear regression analysis of the data gathered from apple slices. Finally, convective heat transfer coefficients were determined. The average convective heat transfer coefficient values for apple slices were calculated as 2.863 W/m(2) degrees C for open sun drying under natural convection mode, 2.065 W/m(2) degrees C for greenhouse drying under natural convection mode, 2.724 W/m(2) degrees C for greenhouse drying under forced convection mode, respectively. The convective heat transfer coefficient in open sun drying was slightly higher than forced convection in greenhouse drying. The convective heat transfer coefficient in greenhouse drying under natural mode was found as the lowest one.
Keywords: Convective heat transfer coefficient; drying; forced convection; natural convection; greenhouse; open sun; apple